2020
DOI: 10.33151/ajp.17.799
|View full text |Cite
|
Sign up to set email alerts
|

Trained, Ready but Under-Utilised: Using Student Paramedics during a Pandemic

Abstract: The aim of this commentary is to outline a case for student paramedics as a potential solution to the operational resource issues ambulances services and other healthcare institutions are expected to experience during high demand situations, such as pandemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…University develops a sense of community and provides a platform for immense social growth and expression, both of which are vital to student success (5,6). For paramedicine students, teamwork and positive community engagement is a fundamental aspect of their learning journey that increases their employability (7). With in-person learning halted due to COVID-19, students, particularly first-year undergraduates, began to feel isolated and anxious (6).…”
Section: Introductionmentioning
confidence: 99%
“…University develops a sense of community and provides a platform for immense social growth and expression, both of which are vital to student success (5,6). For paramedicine students, teamwork and positive community engagement is a fundamental aspect of their learning journey that increases their employability (7). With in-person learning halted due to COVID-19, students, particularly first-year undergraduates, began to feel isolated and anxious (6).…”
Section: Introductionmentioning
confidence: 99%
“…The sense of community that is developed at university is vital in providing a sense of connectedness for both new and continuing students (7). Creating a positive environment built around collaborative group-focussed learning similar to the high levels of teamwork required in paramedicine is vital for student paramedics as they progress through their learning journey (8). The ability to interact with each other in practical sessions and simulations provides the chance to form strong bonds with peers, ultimately creating a more workforce-ready cohort of students.…”
Section: Connectiveness and Communitymentioning
confidence: 99%
“…A large study from Canada demonstrated that 77.7% of university nursing students were willing to volunteer and work during a pandemic [ 16 ], and in Australia paramedic students expressed a willingness to participate in front-line clinical work during the COVID-19 pandemic [ 17 ]. Still, there is a scarcity of literature evaluating both willingness and involvement among paramedic students’ in public health emergencies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%